Black hole formation and fallback during the supernova explosion of a 40 M[symbol sun] star - Chan, Conrad; Pakmor, Rüdiger; Springel, Volker (The astrophysical journal. Part 2, Letters, 2018)
Fallback in core-collapse supernovae is considered a major ingredient for explaining abundance anomalies in metal-poor stars and the natal kicks and spins of black holes (BHs). We present a first 3D simulation of BH formation and fallback in an “aborted” neutrino-driven explosion of a 40 solar mass zero-metallicity progenitor from collapse to shock breakout. We follow the phase up to BH formation using the relativistic CoCoNuT-FMT code. For the subsequent evolution to shock breakout we apply the moving-mesh code Arepo to core-collapse supernovae for the first time. Our simulation shows that despite early BH formation, neutrino-heated bubbles can survive for tens of seconds before being accreted, leaving them sufficient time to transfer part of their energy to sustain the shock wave as is propagates through the envelope. Although the initial net energy (∼2 Bethe) of the neutrino-heated ejecta barely equals the binding energy of the envelope, ##IMG## [http://ej.iop.org/images/2041-8205/852/1/L19/apjlaaa28cieqn1.gif] $11\,M_ødot $ of hydrogen are still expelled with an energy of 0.23 Bethe. We find no significant mixing and only a modest BH kick and spin, but speculate that stronger effects could occur for slightly more energetic explosions or progenitors with less tightly bound envelopes.
Im Titel ist M[symbol sun] als Abkürzung für die astronomische Maßeinheit Sonnenmasse dargestellt
Gesehen am 11.11.2022